Fresno County Bar Association's Barristers Benefit Ball at the Fresno Metropolitan Museum - Watkins, Howard::::::::: (1988)
Thomas Tusan, Marcia Nagel, John Nagel, Betsy Kimball, Robert Kimball, , Sandra Snyder-Hylton, Rod Hylton, and Diana Tusan